If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + 840x = 1000 Solving 25 + 840x = 1000 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + 840x = 1000 + -25 Combine like terms: 25 + -25 = 0 0 + 840x = 1000 + -25 840x = 1000 + -25 Combine like terms: 1000 + -25 = 975 840x = 975 Divide each side by '840'. x = 1.160714286 Simplifying x = 1.160714286
| ln(sqrt(2x-4))=0 | | (8-3x)x=16 | | (9x-3)-(6x+1)= | | -3n^2-14n-8=0 | | 1/6x-3=-10 | | a(n)=-11+(n-1)7 | | x^2(x^3)=0 | | w-f=g | | 0.00000273=2x^2/5.5-x | | a(n)=65-(n-1)100 | | Tan^2x+4tanx-5=0 | | 2.73=2x^2/5.5-x | | 3x^2+3y^2-6x=0 | | 2/3x-5=1/2 | | 20-17u=16u | | n(8)=(n+2)(4.8) | | (5/8)x=3 | | 5a(2b-7c)= | | G(x)=3ln | | Y+4x=62 | | 0=72x-18x^2 | | y=-0.3x^2-0.7x+1.2 | | 3x(y-9z)= | | 15x^-5y^2/(3x^2)^2*y^-3 | | 14y+7=15y-4 | | -1/4-3 | | 3y-2(y-1)=2(2y-2)+1 | | 4*3+7x=47 | | .2y+11=3-.8y | | 5x^4-23x-42=0 | | 4(2x+1)=3(x-7) | | -10=2x-12 |